Processing and Interpretation of Multichannel Seismic Data from Isfjorden, Svalbard - Asghar, Abrar (The University of Bergen, 2011)
This research project is based on the processing and interpretation of nine 2D multichannel seismic profiles from Isfjorden, acquired in 2008, 2009 and 2010 by the University of Bergen. The first part of the thesis describes the processing of the seismic data, while in the second part a broad seismic interpretation was done in order to define the sedimentary packages and type of geological structures present in the. During the seismic data processing, removal of strong water bottom multiples was one major challenge. These strong water bottom multiples were generated because of the high velocities in the sea bed, which are around 4000 m/s in the study area. These multiples were removed by different processes such as multichannel marine predictive deconvolution, a process that estimates a filter for removal of the water bottom multiples. The rest of the noise present in the data was attenuated by applying various types of filtering such as F-K filtering and time variant BP filtering. In order to improve the signal to noise ratio, some other processes e.g. velocity analysis, pre-stack migration and final frequency filtering were carried out on the seismic data. The processing of the seismic data removed most of the multiple energy and depicts the geological structures in the subsurface down to approximately 2.5 or 3 sec (TWT). In the second part, the processed seismic data were interpreted with the main focus on identification and investigation of the sedimentary successions. The identification of different sedimentary successions present in the subsurface was mostly done on the basis of previous studies carried out in the study area. The interpreted sedimentary successions include Carboniferous-Tertiary units (2 sec TWT) lying on the Devonian and deformed metamorphic basement. The deepest reflector interpreted is assumed to represent the top of Hecla Hoek which has been observed in some of the profiles. The presence of sills (dolerite intrusions) was interpreted as a result of reflections with strong amplitudes. ...